How to treat chronic obstructive pulmonary disease in mild and moderate stage? - Mróz, Robert M. (Przewodnik Lekarza/Guide for GPs, 2010)
The aim of the pharmacotherapy of chronic obstructive pulmonary disease is to alleviate symptoms, improve exercise tolerance and quality of life, decreasing mortality and number of exacerbations. Currently, the most effective treatment is based on bronchodilators i.e. cholinolytics, β2-mimetics and phosphodiesterase inhibitors, corticosteroids and mucolytic agents. Following recent guidelines this should be organized according to the severity of symptoms, the degree of lung dysfunction, and the tolerance of the patient to specific drugs in a stepwise approach. Recently published data provide the evidence supporting the effect of combined therapy on disease modification in early stages of the disease.